A green approach towards the removal of a water pollutant by encapsulation of HBCDD into cyclodextrins: Combined experimental and theoretical studies - Biplab Rajbanshi; Subhadeep Saha; Beauty Mahato; Debadrita Roy; Raja Ghosh; Narendra Nath Ghosh; Tanusree Ray; Mahendra Nath Roy (Green Analytical Chemistry, 2024)
Inclusion complexes of a non-biodegradable water pollutant in hydrophobic cavity of β-cyclodextrin and hydroxypropyl-β-cyclodextrin were prepared and characterized. It revealed the enhancement of its fire resistance property and promoted bio-degradability of the water pollutant molecule. The spectroscopic techniques, 1H NMR, 2D ROESY, HRMS, SEM were employed to establish the inclusion phenomenon. Substantial shifts in IR stretching frequency support the inclusion process. The confirmation about the 1:1 stoichiometry of inclusion complexes was obtained from HRMS measurement. Surface texture properties of the inclusion complexes were studied by SEM and the presence of bromine were proved by EDXS. Thermal stability of the inclusion complexes have been illustrated by DSC. The biodegradability study confirms the conversion of non-biodegradable HBCDD into biodegradable material by encapsulating in the two cyclodextrins, i.e., HBCDD get exposed to the microorganism that makes them biodegradable in nature. Furthermore, our theoretical calculations suggest HBCDD formed stable inclusion complexes with both β-CD and HP-β-CD and is concordant with our experimental observations.